What late medieval chant manuscripts do to a present-day performer of plainchant - Vanden Abeele, Hendrik Elie (Leiden Universiteit Leiden, 2014)
This book is witness to Hendrik Vanden Abeeles research into the development, construction and creation of a present-day performance practice of late medieval plainchant, based partly on his work with the Belgian chant group Psallentes. The study focuses on sometimes very specific aspects of the performance of plainchant, relating to a rich and diverse body of chant manuscripts. Meanwhile, the constantly recurring personal storytelling draws a picture of research-acts as ingrained characteristics of the every day activities of a musician. The many challenges and obstacles faced when performing plainchant may turn into opportunities, where the performer fills in the blanks with ideas, colours and textures. He may even be tempted to draw outside the lines, countering any practical or historical constraints in a creative way.
Proefschrift ter verkrijging van de graad van Doctor aan de Universiteit Leiden op gezag van de Rector Magnificus prof. mr. C.J.J.M. Stolker, volgens besluit van het College voor promoties te verdedigen op 15 december 2014.